Pengaruh Pemberian Sari Kurma Terhadap Peningkatan Kadar Hb pada Ibu Hamil - Irmawati S; Rosdiana Rosdiana (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Anemia in pregnancy can have harmful effects on the mother and the fetus. The dangers of anemia in pregnancy can occur with abortion, prematurity of labor, easy infection, the threat of decompensation of hemoglobin less than six, hydatidiform mole, hyperemesis gravidarum, antepartum bleeding, and rupture of membranes. The research objective was to determine the effect of date palm juice on the increase in hemoglobin levels in pregnant women at Barrang Lompo Public Health Center Makassar. The research method used was pre-experimental with a one-group pretest post-test design. This study used an intervention study group, namely the group giving date palm juice to pregnant women. The results of the research of fifteen respondents showed that there was an increase in hemoglobin levels in pregnant women after being given date palm juice at the Barrang Lompo Health Center. pregnancy can increase Hb levels in pregnant women.